The role of lipoproteins in stages of women life - (:unkn) unknown (Nova Science Publishers, Inc, 2011)
Cardiovascular disease, especially atherosclerosis is a consequence of multiple metabolic disorders. Polycystic ovary syndrome (PCOS) is the most common hormonal disorder of reproductive aged women, affecting 5-10% of this population. PCOS traditionally a reproductive disorder showing hyperandrogenism, infertility and chronic anovulation is now considered as a multifaceted disease with metabolic and cardiovascular long term consequences. Dyslipidemia, hypertension, endothelial dysfunction, low grade chronic inflammation are risk factors for cardivascular problems. Dyslipidaemia is very common in patients with polycystic ovary syndrome. It has been suggested that atherogenic lipoprotein abnormalities may be found in one third of women with PCOS who have normal lipid profile. Determination of high risk population may be important for preventive therapy and may provide reduction of cardiovascular risks. Lifestyle interventions play an important role in the prevention of metabolic complications. Moderate-intensity exercise without significant weight loss was found to have beneficial effects on lipoprotein profiles of women with PCOS. Metabolic syndrome is associated with increased risk for cardiovascular disease and type 2 diabetes mellitus. The role of lipoproteins is important in the management of the syndrome. Many combinations of drugs have been studied to treat dyslipidemia and reduce cardiovascular risk. Aging and menopause are the main causes that lead to an adverse lipid profile in women. The incidence of coronary heart disease increases after menopause and obesity may exaggerate the unfavorable lipid profile. Diet and lifestyle changes should be recommended as first line therapy. Treatment should be individualised for each patient and if the lipid profile can not be improved drug therapy should be added. The importance of the lipoproteins should be kept in mind to lower coronary heart disease in stages of women life. © 2010 Nova Science Publishers, Inc.